Governance structure, foreign ownership, audit quality, and firm valuation: Evidence from Vietnam’s emerging market - Phi, Anh Thi Kieu; Nguyen, Thuy Thanh; Bui, Nguyet Minh; Tien, Hung Pham (Asian Development Policy Review, 2026)
This study examines how governance structure, foreign ownership, and audit quality jointly influence firm value in the context of Vietnam’s emerging market, where institutional constraints and information asymmetry remain pronounced over time. Using a panel of 1,603 firm-year observations from listed non-financial companies over the period 2017–2023, the study investigates the impact of board size, foreign ownership, audit opinion, and audit firm rotation on firm value. To address concerns about heteroscedasticity and autocorrelation, the study employs a panel regression model and estimates using feasible generalized least squares (FGLS), thereby enhancing the reliability of the empirical results. The findings indicate that board size, foreign ownership, audit opinion, and audit firm rotation all have a positive and statistically significant impact on firm value. This suggests that both internal monitoring and external audit assurance play complementary roles in fostering investor confidence and enhancing corporate value, particularly in fragile institutional environments. Based on these results, the study recommends coordination between enterprises, management agencies, and investors to improve the market value of enterprises. From a policy perspective, the findings offer actionable insights for regulatory reforms aimed at strengthening corporate governance, disclosure standards, and external audit quality to support the sustainable development of capital markets in Asian emerging economies.